ARCHER 1009 Subset Analysis and LUX-8 Lung: Erlotinib Compared With Dacomitinib or Afatinib - Boltz, Kathy (MD Conference Express, 2015)
The subgroup of patients with the EGFR-activating mutation in exon 19 or 21 appeared to have a favorable trend for dacomitinib vs erlotinib in progression-free survival. Afatinib was favored over erlotinib for second-line treatment of advanced squamous cell carcinoma in terms of progression-free survival, overall response rate, and disease control rate.